THE RELATIONSHIP BETWEEN PHONEMIC STRUCTURES AND SEMANTIC INTERPRETATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
his article explores the semantic functions of speech sounds andphonemes and their critical role in distinguishing meaning in language. Phonemes, as thesmallest units of sound that differentiate words, provide the basis for semanticdifferentiation—subtle shifts in sound can alter meaning, as in minimal pairs like "bat" and"pat." The article also discusses the influence of suprasegmental features (e.g., pitch, stress,and intonation) on meaning, highlighting how they add emotional and contextual layers tolanguage. In addition, the concept of phonesthemes illustrates how certain sound clustersmay carry semantic associations across different words (e.g., "gl-" in "glow" and "glitter,"often related to light). The piece further contrasts phoneme functions across languages,noting how certain languages rely more on specific phonetic distinctions than others, whileacknowledging the influence of morpheme-phoneme interactions and language evolutionon meaning. This analysis enriches our understanding of how languages use sound tocommunicate complex meanings and emotions.